Provincial Human Development Index, a Guide for Efficiency Level Analysis: The Case of Iran - Asma Sabermahani; Mohsen Barouni; Hesam Seyedin; Aidin Aryank Hesal (Tehran University of Medical Sciences, 2013)
Background: Human Development Index (HDI) is a composite indicator that can show the impact of economic strategies on human life standards. The index is calculated by three main factors of income, education and health. This research studies the status of HDI across the Iranian provinces, its changes over time and the efficiency of provinces in using resources.Methods: The data for 2001 and 2009 was obtained from the Iranian Center of Statistics. Data envelopment analysis technique was used to analyze the data. To calculate the efficiency, Banker, Charnes and Cooper's model was used.Results: The national mean for the HDI in 2001 was 0.717 while it grew to 0.747 in 2009. Except for one province, all others had an improved human development index. Low ranked provinces such as Sistan & Baluchistan and Kurdistan stayed at the bottom in 2009 as well. Some provinces such as Bushehr with developing oil industries, or those purposively benefited from national oil income showed good growth. In some provinces, such as Hormozgan, out-migration of manpower to its neighboring province, Bushehr, was associated with decrease of the provincial income level. The number of efficient provinces increased from 5 to 13 in 2009.Conclusion: Iran falls among countries with high human development index based on the 2009 data. However, the distribution of HDI status across provinces was highly varied and the difference between high- and low-developed provinces increased in 2009. The government needs to revise policies concerning distribution of resources among the provinces.